Characterization and Quantification of Gas Hydrates in the California Borderlands. Issue 6 (13th March 2020) - Kannberg, P. K.; Constable, S.
Abstract: Electromagnetic methods are directly sensitive to electrically resistive gas hydrates and can be used to characterize and quantify hydrate deposits. Using a 1 km long deep‐towed marine electromagnetic system, six survey lines were acquired coincident with legacy seismic reflection data in the Santa Cruz Basin in the Outer California Borderlands. While the strongest seismic indicators place hydrate in the central basin, resistors inferred to be hydrate are located predominantly on the flanks of the basin, coincident with gas migration pathways such as faults and steeply dipping strata. Two features consistent with the resistivity profile from previously imaged seafloor methane seeps were also found. Resistivity is related to hydrate saturation through Archie's law, and total hydrate volume of the Santa Cruz Basin is estimated to be 980 × 10 9 m 3 of gas in place. Plain Language Summary: Gas hydrate is a mixture of methane gas (i.e., natural gas) and water that solidifies at high pressures and cold temperatures, such as in shallow marine sediments at depths greater than about 500 m. There is a lot of hydrate on Earth, but our understanding of where it is, and how much there is, is still evolving. As these hydrate deposits can affect the global carbon cycle, climate change, and submarine landslides, understanding the distribution of these deposits is vital. Hydrate is electrically resistive, which means it can be detected by transmitting an electric field in the ocean and recording the strength of that field on a series of instruments. The resulting data are used to construct electrical resistivity models of the Earth. These resistivity models tell us where, and how much, hydrate is located in our study area (the Santa Cruz Basin, located offshore Southern California). We found that the total volume of natural gas held in these hydrates is roughly a trillion cubic meters, enough to fill Dallas Cowboys stadium with natural gas over three hundred thousand times. Key Points: Marine‐controlled source electromagnetics are capable of finding and quantifying gas hydrate resources Hydrates are concentrated at structural highs, where regions of highest concentration are not correlated to seismic indicators of hydrate The Santa Cruz Basin, offshore Southern California, contains an estimated 980 × 10 9 m 3 of gas in place